Cheryl the Christmas tree fairy - Meadows, Daisy (New York : Scholastic Inc., 2012)
"Rachel and Kirsty are staying at a cozy cabin in the woods for Christmas! But everything is going wrong. Even their Christmas tree is missing! The girls think they know who's causing all the holiday trouble ... and they're right! Jack Frost and his goblins have stolen Cheryl the Christmas Tree Fairy's magic tree, star, and gift. Without them, Christmas won't be festive or fun. Can Rachel and Kirsty help Cheryl, or will Jack Frost make this Christmas a catastrophe?"--Page 4 of cover.
Ages 6-9.
720
Accelerated Reader
Keywords: Jack Frost -- (Legendary character) -- Juvenile fiction; Jack Frost -- (Legendary character); Tate, Kirsty (Fictitious character) -- Juvenile fiction; Walker, Rachel (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Christmas trees -- Juvenile fiction; Christmas trees; Fairies; Magic; Fairies -- Fiction; Fantasy; Magic -- Fiction; Christmas stories; Fantasy fiction; Fiction; Juvenile works; Fantasy